Current problems of running training of qualified track and field jumpers - Salamatov M.B. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identifying current problems in the running training of highly qualified track and field jumpers specializing in the running triple jump, identifying areas for improvement in this jumping discipline. Methods and structure of the study. A survey of the competitive activity of track and field jumpers in four jumping disciplines for men and women was carried out at all-Russian competitions in the period 2003-2023. Highly qualified jumpers and jumpers (6 athletes in each jumping discipline) took part in the study. Results and conclusions. After conducting a survey of the competitive activity of leading Russian triple jumpers with registration of the speed parameters of the run-up sections, as well as the implementation of the run-up speed indicators in the support-flight part of the jump, it was concluded that among jumpers, running and technical training in the run-up phase are the main problem limiting the growth of sports jumper skills. An analysis of the competitive activity of leading Russian triple jumpers showed that low speed in the last section of the run-up, which is a consequence of imperfect running structure and technical training in the run-up phase, is the main problem limiting the growth of sportsmanship in this jumping discipline of athletics.